STUDENT SATISFACTION REVIEW FROM INFRASTRUCTURE, ADMINISTRATION SERVICES AND TEACHER COMPETENCY - Diah Putri Pancasani; Supawi Pawenang; Istiatin Istiatin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze whether infrastructure, administrative services and teacher competence have an effect on student satisfaction at the Surakarta Special Program Batik Junior High School simultaneously and partially. This study uses independent variables, namely infrastructure, administrative services and teacher competence. The dependent variable is student satisfaction. The sample of this study were students of the Surakarta Special Program Batik Middle School with the Non Probability Sampling technique with the type of Purposive Sampling. Data was collected using a closed questionnaire which was distributed directly to students with 16 questions. This study uses data analysis methods, namely Descriptive Analysis Method, Validity and Reliability Test, Statistical Analysis Method using Multiple Linear Regression Analysis, with hypothesis testing F Test, t test and Determination Test (R2). The results showed that infrastructure, administrative services and teacher competence had an effect on student satisfaction simultaneously. Partially, administrative services and teacher competence have an effect on student satisfaction, while infrastructure has no effect. This shows that the infrastructure facilities at the Surakarta Special Program Batik Junior High School are still not good so it needs to be improved.